Positive effect of chewing gum on the recovery of intestinal peristalsis in post-laparotomy patients : pre-experimental study - Widiyono; Ranti Ningsih Sumarni; Anik Suwarni; Sulomo (Alma Ata University Press, 2026)
Background: Laparotomy is an invasive treatment that involves surgery on the lining of the abdominal wall. The effect of laparotomy using general anesthesia is gastrointestinal motility and vomiting, and if it lasts more than 24 hours, and causes postoperative ileus (IPO). Chewing gum is a form of artificial feeding to stimulate the intestinal recovery process after surgery. A preliminary study at Waras Wiris Regional Hospital in Boyolali revealed that there were cases of post-appendectomy patients who experienced decreased or no increase in intestinal peristalsis.Various efforts are needed to accelerate the return of intestinal peristalsis in post laparotomy patients to accelerate flatus time, including developing independent nursing interventions for chewing gum. Objectives: This research examined how chewing gum affected intestinal peristalsis in Waras Wiris Hospital post-laparotomy patients. Methods: This quantitative pre-experimental research used a one-group pre- and post-test design. This research sampled 90 postoperative laparotomy patients using purposive sampling. Instruments included a stethoscope, Xylitol gum and observation sheets. All respondents were monitored regularly until they were discharged from the hospital, and the time until the first bowel sound was heard normal bowel sounds, the time until the first gas was passed, the time until the first feeling of hunger, and the time until the first defecation were documented. Surgical data, tolerance of chewing gum after surgery, and postoperative complications was recorded. Data analysis has used the paired t-test. Results: The average value (mean) of digestive peristalsis increased from 0.001 to 16.27 following the intervention. Chewing gum affects intestinal peristalsis in post-laparotomy patients, according to the paired t-test, which had p value of 0.001. Meaning there is an effect of chewing gum on restoration of intestinal peristalsis. Conclusions: Chewing gum may boost intestinal peristalsis after laparotomy